Pengembangan Mina Bisnis Blue Crab (Callinectes sapidus) dengan TTG Blue Crab Boiler Pada UD. Selat Madura 33 untuk Meningkatkan Daya Saing: Development of Blue Crab Mina Business (Callinectes sapidus) with TTG Blue Crab Boiler at UD. Selat Madura 33 to Increase Competitiveness - Mimit Primyastanto; Mariyana Sari; Candra Adi Intyas; Jaisy Aghniarahim Putritamara; Moh. Erfan Arif (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Blue Crab (Callinectes sapidus) is one of the most popular export commodities. One of the activities carried out by crab fishermen is traditional steaming so the steaming time is relatively long and the quality of the crab meat obtained is not good because it contains a lot of water. Therefore, the purpose of this activity is to improve the quality of the crab by using a mechanical boiler. The target partners are Mr. Abd. Malik, the owner of UD. SM 33 (Madura Strait 33). The mechanical steamer machine is a stainless steel frame cabinet model with dimensions of 50 cm x 50 cm x 120 cm which has 5 shelves inside. This service method provides socialization and training on the use of this machine. The results of this activity can improve the skills of partners so that the quality of crab meat is better maintained because it reduces water content by 70% and production cost efficiency by 60%.